2018
DOI: 10.1111/ter.12320
|View full text |Cite
|
Sign up to set email alerts
|

Ground water radon anomalies in Bodrum Peninsula

Abstract: Bodrum Peninsula is located between Hellenic Trench in the west and Gökova Fault Zone in the east which is affected by hundreds of earthquakes every year. Because of its active environment is allowed to monitor tracers/precursors continuously to analyse natural processes. This study focused on the determination of ground water radon (222Rn) concentrations in the Bodrum Peninsula in terms of seismic activities. Radon levels of ten ground water wells were measured periodically throughout the peninsula and these … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 46 publications
0
3
0
Order By: Relevance
“…Radon ( 222 Rn) exists at varying activity concentrations in geological environments, and it is a unique ultra-trace component for tracking geodynamic events. The migration of radon from rock, soil, and groundwater to the atmosphere has been examined as a tool for monitoring seismic and volcanic activity [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…Radon ( 222 Rn) exists at varying activity concentrations in geological environments, and it is a unique ultra-trace component for tracking geodynamic events. The migration of radon from rock, soil, and groundwater to the atmosphere has been examined as a tool for monitoring seismic and volcanic activity [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…Notably, Rn gas anomalies have been observed prior to numerous seismic events, indicating their potential as precursors (e.g., Igarashi et al, 1995;Martinelli, 2020;Ülküm et al, 2018;Zhou et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Field measurements and monitoring have further demonstrated that the spatial and temporal variations of soil gas Rn concentrations and fluxes in active fault zones are closely linked to fault activity (Fu et al., 2017; Wang et al., 2014; Yang et al., 2018). Notably, Rn gas anomalies have been observed prior to numerous seismic events, indicating their potential as precursors (e.g., Igarashi et al., 1995; Martinelli, 2020; Ülküm et al., 2018; Zhou et al., 2016).…”
Section: Introductionmentioning
confidence: 99%